Crossing Time with Philippe de Novare: Deconstructing the Life Cycle in the .iiij. tenz d’aage d’ome - Samuelson, Charlie; Singer, Julie (Viator, 2024)
Abstract Philippe de Novare’s .iiij. tenz d’aage d’ome (ca. 1264) is a treatise on the Ages of Man that stands out not only for its originality but also for the ways in which it performs an unusually intersubjective dynamics of aging. In this text where structural and rhetorical features are persistently looking forward, backward, and askew, Philippe emphasizes intergenerational interdependence: individuals of different age are dependent on each other, and one is effectively in constant negotiation with one’s older and younger selves. Crucially, this interdependence also manifests itself differently for men and women of different social classes. As we suggest through close textual analysis and dialogue with medieval learned culture, as well as queer theory, disability studies, and life course theory, Philippe’s text thus exposes the multiple and variegated temporal modes that, perhaps counterintuitively, aging implicates. As importantly, it draws attention to the precarity of this temporal economy. Indeed, while the .iiij. tenz illustrates that a significantly antilinear conception of aging is not necessarily subversive, it also demonstrates how normative conceptions of aging nonetheless mobilize a complex network of temporal relations that is constantly flirting with its own unraveling. We argue that while Philippe’s treatise ostensibly sets out to define each age in a didactic, orderly mode, it complexly embraces the heterogeneous, unruly temporalities of aging in manners that underscore how nonlinear elements can both sustain and threaten normative temporal schemes